The Effectiveness of the Form Model For the Two Hemispheres of the Brain in the Technical Performance of Some Female Badminton Skills - Akeel Yousef Nasser; Mazen Kadhim Nassif; Wissam Salah Abdul Hussein (Indian Journal of Forensic Medicine & Toxicology, 2021)
Through the presence of researchers in the field of teaching and training for most activities of racket gamesin general, and playing badminton in a special way in the College of Physical Education and Sports Sciences- University of Kerbala, they found that most female students in the second stage suffer from difficultyin performing badminton skills, knowing that it is one of the subjects taught at this stage, and throughextensive study and investigation about finding solutions to this problem, the researchers decided to relyon the application of a teaching model aimed at investing the energies of the brain and dealing with thetendencies and desires of the learner, a research that the educational curriculum addresses all learners, this iswhat motivated the researchers to prepare a new educational curriculum with all its contents according to thecharacteristics of the two hemispheres of the brain using the format model to learn some basic skills for thefemale students in badminton, and the objective of the research is to prepare an educational curriculum usingthe (4MAT) model according to the two hemispheres of the brain to learn some skills of the badminton,and to identify the effectiveness of the educational curriculum by using the (4MAT) model according to thetwo hemispheres of the brain in learning some badminton skills for female students. The researchers usedthe experimental approach by designing (one group with pre and post- test) in order to suit the nature ofthe problem and achieve the research objectives. The most important conclusions were that the educationalcurriculum, using the (4MAT) model according to the two hemispheres of the brain, contributed to learningsome basic skills for female students with badminton. The most important recommendations are the necessityof adopting educational curricula according to the (4MAT) model in learning basic skills with badminton.